A NEW DINOFLAGELLATE FROM THE LATE CRETACEOUS OF THE COLORADO BASIN, OFF SHORE ARGENTINA (Ameghiniana, 2018)
This paper introduces a new dinoflagellate species from the Late Campanian – early Maastrichtian horizons of the Colorado basin: Andalusiella guersteinii Ottone sp. nov. It is a relatively large, fusiform organic-walled cyst, whose apical horn is longer than its antapical, and has a smooth endophragm that is markedly thicker than the periphragm; a peridinioid paratabulation is suggested by the intercalary 2a hexa iso-deltaform archeopyle, the paracingulum, and the flagellar scar. The age of this new species is determined by associated palynomorphs, foraminifers and nannoplankton, but also by radiometric dating.